2015
DOI: 10.1007/s13204-015-0485-8
|View full text |Cite
|
Sign up to set email alerts
|

Bio-inspired green synthesis of Fe3O4 magnetic nanoparticles using watermelon rinds and their catalytic activity

Abstract: Novel and bio-inspired magnetic nanoparticles were synthesized using watermelon rinds (WR) which are nontoxic and biodegradable. Watermelon rind extract was used as a solvent and capping and reducing agent in the synthesis. The Fe 3 o 4 MNPs were characterized by using transmission electron microscopy (TEM), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR) and vibrating sample magnetometer techniques (VSM). XRD studies revealed a high degree of crystalline and monophasic Fe nanoparticles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(21 citation statements)
references
References 28 publications
2
17
0
2
Order By: Relevance
“…The presence of these diffraction peaks suggested highly crystalline nature and coincide with the standard XRD data of iron oxide nanoparticles. Moreover, these observations are also in accordance with the various previous studies proposed by Wei et al [37], Prasad et al [38] and Fatima et al [39]. In addition, similar diffraction peaks were observed in the case of Fe 3 O 4 -MNPs@Si (Fig.…”
Section: Ftir Analysis: Ftir Spectra For the Fe 3 O 4 -Mnps Andsupporting
confidence: 92%
See 1 more Smart Citation
“…The presence of these diffraction peaks suggested highly crystalline nature and coincide with the standard XRD data of iron oxide nanoparticles. Moreover, these observations are also in accordance with the various previous studies proposed by Wei et al [37], Prasad et al [38] and Fatima et al [39]. In addition, similar diffraction peaks were observed in the case of Fe 3 O 4 -MNPs@Si (Fig.…”
Section: Ftir Analysis: Ftir Spectra For the Fe 3 O 4 -Mnps Andsupporting
confidence: 92%
“…Table 1 summaries the elemental composition for MNPs obtained from EDX analysis. Moreover, according to Prasad et al [38] this kind of observation indicates the spherical shape and elemental iron formed by a facile manner. These results also support the SEM analysis where spherical shape for synthesized MNPs was reported.…”
Section: Resultsmentioning
confidence: 96%
“…This observation confirmed the formation of Azadirachta indica mediated Fe 3 O 4 -NPs in one-pot reaction. The FTIR data suggested that the reasonable mechanism of Fe 3 O 4 -NPs formation may be due to the reduction of iron ions that takes place together with the phenolic compounds in the Azadirachta indica leaf extract [53,54].…”
Section: Resultsmentioning
confidence: 99%
“…A partir de lo anterior, se determinó que sí es posible la obtención de magnetita disminuyendo el exceso de 20:1 a 10:1, lo cual se puede identificar en la Figura 2 ya que en el espectro obtenido se observa que los picos característicos de la zona perteneciente a enlaces Fe-O guardan similitudes con respecto al pico de la muestra comercial, como por ejemplo el ancho del mismo, de lo anterior es posible afirmar que se disminuye la generación de ácido acético en un 50% con respecto a la muestra en la que se agregó un exceso de aproximadamente 20:1, exceso que ha sido reportado previamente por diferentes investigaciones como el uso de extractos obtenidos a partir de cáscaras de banano [14], sandía [12] y extracto de semilla de Syzygium cumini [22].…”
Section: Excesosunclassified
“…Por tal motivo se empezó a estudiar un método, que además de evitar el uso de dichos compuestos, aprovecha residuos agroindustriales tales como la cáscara del banano y la sandía conociendo que en estas hay azúcares reductores presentes. Con el fin de concentrar los azúcares, las cáscaras fueron sometidas a un proceso de reflujo a diferentes condiciones, luego de haber removido la humedad, estas se pulverizaron y se disolvieron en cloruro de hierro hexahidratado y acetato de sodio, esta mezcla fue llevada a calentamiento para la posterior obtención de las NPs [12].…”
Section: Introductionunclassified